2022
DOI: 10.1590/1808-057x20211503.pt
|View full text |Cite
|
Sign up to set email alerts
|

Sistema de mensuração de desempenho, satisfação ambiental e engajamento no trabalho verde,

Abstract: RESUMO O objetivo deste artigo foi analisar os efeitos do uso (diagnóstico, interativo e combinado) do performance measurement systems (PMS) na satisfação ambiental e os reflexos disso no engajamento no trabalho verde de funcionários. Estudos sobre sistemas de controle gerencial (SCG) e resultados ambientais têm priorizado variáveis organizacionais, como o desempenho sustentável/ambiental. Esforços direcionados aos SCG para fomentar comportamentos verdes nos funcionários são limitados. Também existe uma chamad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The study by Alves et al (2022) identified that using management controls to share information influences organizational resilience, which is also considered a type of organizational performance. This result was also found by Frare et al (2023) when analyzing the use of formal and informal controls in fintechs, and these controls are responsible for fostering resilience, again considered a proxy for organizational performance.…”
Section: Informal Controls and Organizational Performancesupporting
confidence: 55%
See 1 more Smart Citation
“…The study by Alves et al (2022) identified that using management controls to share information influences organizational resilience, which is also considered a type of organizational performance. This result was also found by Frare et al (2023) when analyzing the use of formal and informal controls in fintechs, and these controls are responsible for fostering resilience, again considered a proxy for organizational performance.…”
Section: Informal Controls and Organizational Performancesupporting
confidence: 55%
“…Although informal controls are tools managers use, their guiding role is worth mentioning. They act in a relevant way for controls in different environments, acting positively regarding organizational performance, whether family businesses , industries (Alves et al, 2022), or fintechs (Frare et al, 2023). The study by Alves et al (2022) identified that using management controls to share information influences organizational resilience, which is also considered a type of organizational performance.…”
Section: Informal Controls and Organizational Performancementioning
confidence: 99%
“…The findings of this study have implications for both research and practice. Research concerned about the environmental effects of organizational actions has paid increased attention to the understanding of determinants of employees' PEB at work (Paillé & Boral, 2013;Wesselink et al, 2017;Tian & Robertson, 2019;Frare et al, 2022). This paper adds to this literature by showing whether and how the social pressures exerted by a value statement can affect employees' intention to follow PEB.…”
Section: Discussionmentioning
confidence: 92%
“…Yet, prior studies (e.g., Kachelmeier et al, 2016;Akyniele et al, 2020) show that the effects of value statements depend on the presence of formal controls. In addition, prior studies have shown that formal controls can also affect PEB at work (e.g., Aguiar, 2021;Frare et al, 2022). Then, future studies could examine the effects of value statements on activated personal norms and PEB at work in the presence of incentive schemes based, for instance, on environmental performance measures (Rodrigue et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation